Pengaruh Proses Rekrutmen dan Seleksi terhadap Kinerja Karyawan : Studi pada PT. Dian Bahari Sejati - Muhammad Darwis Meyandie Nasution (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
Based on the data processing hasi it is known that the selection in which the company has an influence on employee performance partially . The most dominant variable affecting the performance of employees, especially in PT. Dian Bahari Sejati is the selection , the reason for the selection of variables having the largest value of the regression coefficient when compared with variable recruitment , so that the second hypothesis can be said to be proven . Simultaneously, it is known that the process of recruitment and selection simultaneously have an influence on the performance of employees at PT. Dian Bahari Sejati.The influence of variables X1 ( recruitment ) to variable Y ( company performance ) indicated by the value of the correlation coefficient ( r xy ) of 0.727 . While the R -square is 0.528 or 52.80 % , showing approximately 52.80 % variable Y ( the performance of the company's employees ) can be explained by the recruitment process variable ( X1 ) , or in practice it can be said that the contribution of the recruitment process ( X1 ) to variable Y ( performance of employees ) is 52.80 % . The rest is influenced by other variables not examined . The influence of X2 ( selection) to variable Y ( the performance of employees ) indicated by the value of the correlation coefficient ( r xy ) of 0.655 . While the R -square is 0.429 or 42.90 % , showing approximately 42.90 % variable Y ( the performance of the employee ) can be explained by the selection of variables ( X2 ) , or in practice it can be said that the contribution of selection (X2 ) to variable Y ( employee performance ) is 42.90 % . The rest is influenced by other variables not examined .The influence of variables X1 ( recruitment ) and X2 ( selection) to variable Y ( the performance of employees ) indicated by the multiple correlation coefficient of 0.565 , while the R -square value is 0.319 or 31.90 % , showing approximately 31.90 % variable Y can be explained by the recruitment process variable ( X1 ) and selection (X2 ) to variable Y ( the performance of the employee ) is 31.90 % . The rest is influenced by other variables not examined . Or proposed hypothesis can be accepted or recruitment process and se ; of selection has a positive and significant effect on the performance of employees at PT. Dian Bahari Sejati.